A thoughtful profession the early years of the American Philosophical Association - Campbell, James 1948- (Open Court, 2006)
"Chronicles the activities of the American philosophical associations founded at the beginning of the twentieth century that merged into the present American Philosophical Association in 1927. The field of philosophy's development as a profession, its relation to domestic and international politics, and the evolution of its ideas and ideals are discussed"--Provided by publisher.
Chronicles the activities of the American philosophical associations founded at the beginning of the twentieth century that merged into the present American Philosophical Assocation in 1927. The field of philosophy's development as a profession, its relation to domestic and international politics, and the evolution of its ideas and ideals are discussed
Includes bibliographical references and index
Keywords: American Philosophical Association -- History -- 20th century; American Philosophical Association; Geschichte 1900-2000; Geschichte 1892-1930; Geschichte; Philosophie; Philosophy, American -- Societies, etc -- History -- 20th century; Philosophy -- United States -- Societies, etc -- History -- 20th century; USA